Young people and housing: identifying the key issues. Issue 2 (2nd April 2016) - Mackie, Peter K.
Abstract : The housing experiences of young people are a contemporary global concern, with the exacerbation of young people's housing problems in many countries reported widely in the media and raising important policy questions. In response, this special issue of the International Journal of Housing Policy presents new empirical research from Europe and East Asia and seeks to identify key areas for improvement in national housing policies. This editorial summarises the main housing issues identified in the special issue articles and identifies the emergence of two cross-cutting policy challenges. The first challenge is to ensure all young people have an equal opportunity to leave the family home and live independently. This will require a much greater awareness of the political, economic and cultural forces restricting young people's transitions. The second key policy challenge is to improve the suitability and availability of housing for young people, with studies in this special issue specifically pointing towards an improved private rented sector and further provision of shared housing. Articles in this special issue indicate that a failure to respond to these significant housing policy challenges will have wide reaching social and economic consequences.